Zinc deficiency predicts new-onset diabetic kidney disease in type 2 diabetes: a retrospective cohort study - Hung, Kuo-Chuan; Yu, Ting-Sian; Hsu, Chih-Wei; Lai, Yi-Chen; Tan, Ping-Heng; Lin, Yao-Tsung; Wang, Li-Kai; Lin, Chien-Ming; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a major global health challenge, with diabetic kidney disease (DKD) representing one of its most serious complications. Although zinc deficiency is common in diabetes, large-scale clinical evidence on its role as a predictor of new-onset DKD is limited.MethodsWe conducted a retrospective cohort study using the TriNetX Analytics Network Platform to analyze patients aged ≥18 years who underwent zinc testing (2010–2023). Patients were classified into zinc deficiency (serum zinc <70 μg/dL) and control groups (70–120 μg/dL). After 1:1 propensity score matching, we analyzed the risk of new-onset DKD at two-year follow-up. The secondary outcomes included the risks of all-cause mortality, acute kidney injury (AKI), chronic kidney disease (CKD), poor glycemic control (HbA1c ≥ 7%), and ophthalmic complications.ResultsThe final matched cohort included 20,470 patients (10,235 per group) with a mean age of 54 years. Zinc deficiency was associated with a 42% increased risk of new-onset DKD (hazard ratio [HR] 1.42, 95% confidence interval [CI]: 1.20–1.68, p < 0.001). Additional significant associations included all-cause mortality (HR: 1.65, 95% CI: 1.40–1.95, p < 0.001), AKI (HR: 1.47, 95% CI: 1.27–1.69, p < 0.001), and CKD development (HR: 1.18, 95% CI: 1.02–1.37, p = 0.028). No significant associations were observed with poor glycemic control or ophthalmic complications. Subgroup analyses showed stronger associations in patients with diabetes duration <5 years (HR 1.65, 95% CI: 1.35–2.02, p < 0.001).ConclusionZinc deficiency is an independent predictor of new-onset DKD and adverse outcomes in T2DM, particularly in early disease. These findings support zinc deficiency as a potential biomarker for risk stratification and highlight the need for prospective studies to evaluate whether zinc supplementation can reduce risk.